Activated carbon supported cobalt catalysts for advanced oxidation of organic contaminants in aqueous solution - Shukla, Pradeep; Wang, Shaobin; Sun, Hongqi; Ang, Ming; Tade, Moses (elsevier, 2010)
A heterogeneous cobalt catalyst was prepared by impregnation of cobalt ion on an activated carbon (AC) and used to activate peroxymonosulphate (PMS) for advanced oxidation of phenol in aqueous solution. The Co/AC catalyst was characterised by several techniques such as XRD, EDS, SEM, and TGA. It was found that Co2O3 was the major form of Co species and was homogeneously distributed on the activated carbon surface. Co/AC exhibited high activity in oxidation of phenol with sulphate radicals and 100% decomposition and 80% TOC removal could be achieved in 60 min at the conditions of 500 ml phenol solution of 25 ppm, 0.1 g catalyst and 1 g peroxymonosulphate. The catalyst also exhibited stable performance after several rounds of regeneration. Several operational parameters such as catalyst and oxidant amount, temperature on the rate of oxidation were found to influence the phenol oxidation.